1986
DOI: 10.1007/bf00123234
|View full text |Cite
|
Sign up to set email alerts
|

C-band variability and phylogeny of Lacertidae

Abstract: The karyology of various species from the family Lacertidae (Reptilia, Sauria) has been studied with conventional and C-banding techniques.The study shows that this family is not so conservative from a karyological viewpoint as considered till now. In fact a higher diploid number than that generally observed in most species of Lacertidae and supernumerary chromosomes have been observed in three of the species investigated. Moreover an evident interand intraspecific variability has been found in the C-banding p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
2

Year Published

1987
1987
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 29 publications
2
22
0
2
Order By: Relevance
“…It is widely distributed throughout southeast Asia inhabiting mainly high grasslands and is registered as 'Least Concern' in the IUCN (International Union for Conservation of Nature and Natural Resources) list (http://www.iucnredlist.org). Previous cytogenetic studies have reported individuals of this species with 2n = 38, 40 and 42 acrocentric chromosomes (Olmo et al, 1986). In contrast to Z, the W chromosome is highly heterochromatic, as revealed from C-banding staining (Olmo et al, 1984(Olmo et al, , 1986Odierna et al, 1985).…”
Section: Studied Species Materials Origin and Ethics Statementmentioning
confidence: 69%
See 1 more Smart Citation
“…It is widely distributed throughout southeast Asia inhabiting mainly high grasslands and is registered as 'Least Concern' in the IUCN (International Union for Conservation of Nature and Natural Resources) list (http://www.iucnredlist.org). Previous cytogenetic studies have reported individuals of this species with 2n = 38, 40 and 42 acrocentric chromosomes (Olmo et al, 1986). In contrast to Z, the W chromosome is highly heterochromatic, as revealed from C-banding staining (Olmo et al, 1984(Olmo et al, , 1986Odierna et al, 1985).…”
Section: Studied Species Materials Origin and Ethics Statementmentioning
confidence: 69%
“…Previous cytogenetic studies have reported individuals of this species with 2n = 38, 40 and 42 acrocentric chromosomes (Olmo et al, 1986). In contrast to Z, the W chromosome is highly heterochromatic, as revealed from C-banding staining (Olmo et al, 1984(Olmo et al, , 1986Odierna et al, 1985).…”
Section: Studied Species Materials Origin and Ethics Statementmentioning
confidence: 69%
“…Intestines, spleens, lungs, and gonads were removed and incubated for 30 min in a 0.7% sodium citrate solution. Chromosomes were obtained by air drying and scraping as described by Olmo et al (1986). Besides conventional staining (5% Giemsa at pH 7), the following techniques were applied: (1) AgNO 3 -banding of NORs following Howell and Black (1980); (2) staining with the C+G specific fluorochrome chromomycin A 3 (CMA 3 ) according to Sahar and Latt (1980), with a reduced exposure (a few seconds) to the non fluorescent dye, methyl green; (3) the A+T specific fluorochrome, DPI/ distamycin (DA), and CMA 3 /DA (DAPI: Schweizer 1976); (4) C-banding as described by Sumner (1972), incubating the slides for 5 min at 45°C in Ba(OH) 2 ; (5) in situ digestion with Alu I endonucleases (compare Mezzanotte et al 1983).…”
Section: Methodsmentioning
confidence: 99%
“…One male showed a variable number of chromosomes due to one or two extra microchromosomes (Table 1), and an increase of chiasma frequency in the A chromosomes was also observed. Olmo et al (1986) found individuals of the species Takydromus sexlineatus (Thailand) and Lacerta lepida (Spain) bearing supernumerary microchromosomes (Table 1). Mitotic plates with 38, 40 and 42 chromosomes were observed in Takydromus sexlineatus; however at diplotene cells only 20 or 21 bivalents were present.…”
Section: Conventionally Stained Karyotypes and B Chromosomes In Lizardsmentioning
confidence: 99%